Temperature Calculation in Respect of Basic Elements of Power Oil Transformer on the Basis of Its Tank Surface Temperature Analysis - D. I. Zalizny; O. G. Shirokov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a real-time calculation algorithm of oil, winding and magnetic core temperature of power transformer on the basis of measured values of tank surface temperature and air temperature without measuring current. The algorithm is based on the calculation of the equivalent load factor of the transformer. Imitation simulation has confirmed efficiency of the algorithm. After tests on functioning transformers the algorithm can be used in thermal protection devices and diagnostic devices for power oil transformers.